Assault on the Catalan Parliament: Catalan Nationalism versus Spanish Democracy. Issue 2 (3rd April 2022) - Ortega, David
ABSTRACT: Although not as renowned as the assault on the United States Capitol on January 6, 2021, on October 27, 2017 some of the elected representatives of the Catalan Parliament, those who are in favor of Catalonia's independence from Spain, unilaterally declared Catalonia's independence against the Spanish Constitution, Spanish laws and the decisions of the courts. This article studies the main violations of Spanish democracy that occurred in those three years from 2015 to 2017, plunging Catalonia into a territory at the edge of security and democracy.